Molecular and population genetic analyses of beta-thalassemia in Turkey - (:unkn) unknown (WILEY, 1998)
In this report we describe the molecular analysis of 795 chromosomes derived from unrelated Turkish beta-thalassemia and sickle cell anemia carriers identified in hematology clinics in Istanbul, Ankara, Izmir, Adana, and Antalya, The determination of the molecular pathology of 754 beta-thalassemia and 42 abnormal hemoglobin genes and analysis of the frequency distribution in six distinct regions of Turkey was accomplished, The experimental strategy, based on PCR amplification of the beta-globin gene, included dot-blot hybridization with 18 probes specific for the Mediterranean populations, denaturing gradient gel electrophoresis, and genomic sequencing. When the regional results are compared with the overall frequency of mutations in the country, it is observed that the frequencies in the western and southern parts of Turkey are in good accordance with the overall distribution, whereas the northern and eastern parts have a more region/population-specific profile with some rare mutations having a significantly high occurrence in these regions, Further evaluation of the data with respect to region- or population-dependent differences will contribute to a better understanding of the mechanisms leading to the marked genetic heterogeneity in Turkey, but could also be extremely valuable in facilitating rapid identification of mutations in families at risk for different hemoglobinopathies. (C) 1998 Wiley-Liss, Inc.
Keywords: Turkey; beta-thalassemia; sickle cell anemia; SICKLE-CELL ANEMIA; PRENATAL-DIAGNOSIS; TURKISH PATIENT; AMPLIFIED DNA; GLOBIN GENES; MUTATIONS; DELETION; PROBES; BP